Caregivers’ challenges in engaging with the health system to optimise medication management of older care recipients: a qualitative study including home visits - Marja Airaksinen; Marika Pohjanoksa-Mäntylä; Sirkka-Liisa Kivelä; Shane Desselle; Annika Kiiski; Elisa Luoma (BMJ Open, 2025)
Objectives Medication management is a demanding task for family caregivers of older adults, adding to their care burden. The aim was to identify the challenges family caregivers experience in managing medications of older care recipients to obtain caregiver-centred evidence for developing social and health services to meet their needs.Design The qualitative data were collected during two consecutive home visits using thematic interviews with a narrative approach during the period of October 2017 to September 2018. The interview data were qualitatively analysed using the framework method with a combination of the inductive and deductive approaches. Human error theory with systems approach and prospective risk management was used as a theoretical framework.Setting Family caregiving of older adults.Participants 21 officially contracted family caregivers and their older (≥65 years) care recipients using >1 prescription medicine from the capital region of Finland.Results Three conceptual models were constructed: (1) to position family caregiving in the public social and healthcare system, (2) to identify challenges and (3) needs for development in medication management prioritised from challenges. Family caregivers were not well integrated as a part of the health system, but left alone to manage the care recipient’s medications. When urgent treatment-related matters arose, caregivers were not able to reach the physician. The major development needs concerned (1) identification of the caregivers as family caregivers in healthcare and community pharmacies, (2) making familiar healthcare professionals accessible, (3) ensuring sufficient customised support for managing medications at home (up-to-date medication list, monitoring and medicines information), (4) more active involvement and communication in the care process and (5) adopting compatible electronic health records between primary and secondary care, and pharmacies and social services.Conclusions Family caregiving practices and support services should be developed in cooperation with the caregivers to meet their needs and place the families at the centre of the medication use process. Strengthening the integration of family caregiving to the social and healthcare system is vital, for example, by making easy access to family physician and involving pharmacists more actively in supporting medication management.